Development of Ti-10Nb alloy by powder metallurgy processing route for dental application - Kumar R.; Gautam R.K. (My University, 2025)
Titanium and its alloys are used to make dental implants because of its low density, high strength, and corrosion resistance. This paper describes the development of a potential biomaterial Ti-10Nb by powder metallurgy utilizing four different compaction pressures and analyses its microstructural, physical, mechanical, electrochemical, biological, and tribological behavior under various situations. The alloys were fabricated using four different compaction pressures, that is, 600, 650, 700, and 750 MPa, and sintered in a vacuum atmosphere at 1000°C for 1.5 h. The density of the samples was measured using Archimedes principle. X-ray diffraction and scanning electron microscopy equipped with energy dispersive spectroscopy were used to investigate the phase composition and microstructure, and a profilometer was used to examine the surface roughness of various samples. Vickers hardness tester was used to evaluate hardness, and a universal testing machine was used for compression testing. Corrosion and wear behavior were examined using a potentiostat and a Bio-Tribometer, respectively. This Ti-10Nb alloys consist of α + β phase, and have 16% highest porosity in sample compacted at 600 MPa. The samples compacted at 750 MPa achieved highest hardness, yield strength, compressive strength, and elastic modulus of 450 ± 29.72 HV, 718.22 ± 16.37 MPa, 1543.59 ± 24.37 MPa, and 41.27 ± 3.29 GPa, respectively. In addition, it also possesses highest corrosion and wear resistance with lowest icorr of 0.3954 ± 0.008 μA/cm2 and wear volume of (31.25 ± 0.206) × 10−3 mm3. These results indicate that the developed alloys have a variety of desirable properties, including high hardness, adequate compressive strength, good corrosion and wear resistance, apatite-forming capability, and a low elastic modulus, which is advantageous for avoiding stress shielding. Therefore, it may be recommended to use it as a dental implant material. © 2023 Wiley Periodicals LLC.